The Different Roles of Penicillium oxalicum LaeA in the Production of Extracellular Cellulase and β-xylosidase - Li, Yanan; Zheng, Xiaoju; Zhang, Xiujun; Bao, Longfei; Zhu, Yingying; Qu, Yinbo; Zhao, Jian; Qin, Yuqi (Frontiers in Microbiology, 2016)
Cellulolytic enzyme hydrolysis of lignocellulose biomass to release fermentable sugars is one of the key steps in biofuel refining. Gene expression of fungal cellulolytic enzymes is tightly controlled at the transcriptional level. Key transcription factors such as activator ClrB/CLR2 and XlnR/XYR1, as well as repressor CreA/CRE1 play crucial roles in this process. The putative protein methyltransferase LaeA/LAE1 has also been reported to regulate the gene expression of the cellulolytic enzyme. The formation and gene expression of the cellulolytic enzyme was compared among Penicillium oxalicum wild type (WT) and seven mutants, including ΔlaeA (deletion of laeA), OEclrB (clrB overexpression), OEclrBΔlaeA (clrB overexpression with deletion of laeA), OExlnR (xlnR overexpression), OExlnRΔlaeA (xlnR overexpression with deletion of laeA), ΔcreA (deletion of creA), and ΔcreAΔlaeA (double deletion of creA and laeA). Results revealed that LaeA extensively affected the expression of glycoside hydrolase genes. The expression of genes that encoded the top 10 glycoside hydrolases assayed in secretome was remarkably downregulated especially in later phases of prolonged batch cultures by the deletion of laeA. Cellulase synthesis of four mutants ΔlaeA, OEclrBΔlaeA, OExlnRΔlaeA, and ΔcreAΔlaeA was repressed remarkably compared with their parent strains WT, OEclrB, OExlnR, and ΔcreA, respectively. The overexpression of clrB or xlnR could not rescue the impairment of cellulolytic enzyme gene expression and cellulase synthesis when LaeA was absent, suggesting that LaeA was necessary for the expression of cellulolytic enzyme gene activated by ClrB or XlnR. In contrast to LaeA positive roles in regulating prominent cellulase and hemicellulase, the extracellular β-xylosidase formation was negatively regulated by LaeA. The extracellular β-xylosidase activities improved over 5-fold in the OExlnRΔlaeA mutant compared with that of WT, and the expression of prominent β-xylosidase gene xyl3A was activated remarkably. The cumulative effect of LaeA and transcription factor XlnR has potential applications in the production of more β-xylosidase.